(untitled) (PerCursos, 2022)
Promote the appreciation of geodiversity and its geomorphological heritage in trails of conservation units, with emphasis on National Parks, from an interdisciplinary perspective, is extremely importance, as it contributes to the sustainable use and conservation of these territories and their surroundings. Among the attractions of the Serra dos Órgãos National Park (Parnaso), one of the most outstanding in terms of public use in the Petrópolis sector is the trail to the “Castelos do Açu”, which has an expressive potential for scientific dissemination based on environmental interpretation proposals. In this context, based on the bibliographic survey on the history and geodiversity of the territory of Parnaso, and carrying out fieldwork between the years 2017 and 2021, the present study aimed to contribute to the Chico Mendes Institute for Biodiversity Conservation ( ICMBio) in the dissemination and management of geomorphological heritage, from the identification and characterization of points of interest of geodiversity on the trail to “Castelos do Açu”, systematizing such information with the Wikiloc® navigation app aid for the promotion of geotourism, making it possible to re-signify existing visitation. The study made it possible to highlight that although geodiversity is often perceived by the public as a static approach, in mountain trails a broader interpellation is needed from the perspective of geomorphological processes. The results generated are associated with dissemination strategies and studies under development on other trails, where the geosystemic approach to environmental interpretation is being highlighted.